2009
DOI: 10.1519/jsc.0b013e3181b3ddbf
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Physical Performance–Related Variables in Male NCAA Division III Soccer Players

Abstract: The purpose of this study was to examine changes in various aerobic and anaerobic physical performance measures in male National Collegiate Athletic Association (NCAA) Division III soccer players during the competitive soccer season. Twelve starters of the men's soccer team (mean +/- SD; age = 20.0 +/- 0.9 years, height = 175.7 +/- 8.1 cm, body mass = 73.9 +/- 11.00 kg, body mass index [BMI] 24.0 +/- 3.0 kg.m2, and percent body fat = 10.6 +/- 5.4%) were tested at the beginning (PRS) and the end (POS) of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 10 publications
1
37
0
3
Order By: Relevance
“…Three-corner run test used in this study assesses the speed endurance and anaerobic endurance in football players (Rösch et al, 2000, Taskin, 2009). The time of completion of this test by football players was 31.29 s. Some authors used Wingate anaerobic power test to measure the anaerobic performance in football (Gacesa et al, 2009;Magal et al, 2009;Meckel et al, 2009). The Wingate test consists of pedaling for 30 seconds at a maximum effort.…”
Section: Speed-anaerobic Endurance and Balancementioning
confidence: 99%
“…Three-corner run test used in this study assesses the speed endurance and anaerobic endurance in football players (Rösch et al, 2000, Taskin, 2009). The time of completion of this test by football players was 31.29 s. Some authors used Wingate anaerobic power test to measure the anaerobic performance in football (Gacesa et al, 2009;Magal et al, 2009;Meckel et al, 2009). The Wingate test consists of pedaling for 30 seconds at a maximum effort.…”
Section: Speed-anaerobic Endurance and Balancementioning
confidence: 99%
“…More specifically, performance level on soccer-specific tests has been found to correlate with match performance in terms of the distance covered at high-intensity -a key determinant of physical match performances -emphasizing the value of such tests to soccer performance [5,7]. The variation in fitness over the course of a season has been investigated extensively in male soccer players of different playing standard, age and nationality [6,[8][9][10][11]. In general, the existing research on male players has indicated that over the course of a season aerobic performance is improved mid-season, after which a decline is reported; whilst sprint and agility performance improve throughout the competitive season [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The variation in fitness over the course of a season has been investigated extensively in male soccer players of different playing standard, age and nationality [6,[8][9][10][11]. In general, the existing research on male players has indicated that over the course of a season aerobic performance is improved mid-season, after which a decline is reported; whilst sprint and agility performance improve throughout the competitive season [6,[8][9][10][11]. However, much of the research has focused on only few components of fitness, which does not present a holistic evaluation of the players in the respective studies.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7 Stølen et al 1 claim that junior soccer players traditionally have lower VO 2max than seniors. Casajús 8 and Magal et al 9 noted a higher VO 2max at the end of the season, while Heller et al 10 and Metaxas et al 11 reported best VO 2max at the end of preseason or beginning of season. Stølen et al 1 claim that VO 2max among high-performance teams has been elevated over the last decade compared with values reported in the 1980s.…”
mentioning
confidence: 95%